Halal Tourism: Global Market Opportunity in Industrial Revolution 4.0 - Shinta Ilahi, Nurul Anggraeni; Huda, Nurul; Badry, Ahmad Ibrahim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
One of the emerging segments of the halal industry is halal tourism. The rapid development of information and communication technology adds to the opportunity for the global halal tourism market, especially after entering a new stage of the world's transition from pandemic to endemic. Which increasingly opens opportunities for Muslim tourists to visit tourist destinations. Furthermore, the presence of various mobile applications that support information needs for tourist trips also takes apart. This paper aims to analyze the development of global halal market information Global Market Opportunity in the World Halal Tourism area to face the Industrial Revolution 4.0. The presence of the Halal Trip Application is one of the alternatives for tourists to find the information needed before starting a trip. This study uses a literature study approach, case studies on the application of halal trips, and critical theory of technology to analyze the specifications for the use of application products in terms of content and features. The result is that the Halaltrip application helps Muslim tourists. There are other interests besides advancing halal tourism, namely the importance of promoting halal tour packages to 25 countries with 103 tourist attraction destinations.The suitability of the offer of halal tourism destinations with halal tourism criteria does also discussed.